SARS-CoV-2–specific B- and T-cell immunity in a population-based study of young Swedish adults - Björkander, Sophia; Du, Likun; Zuo, Fanglei; Ekström, Sandra; Wang, Yating; Wan, Hui; Sherina, Natalia; Schoutens, Lisanne; Andréll, Juni; Andersson, Niklas; Georgelis, Antonios; Bergström, Anna; et al. (Journal of allergy and clinical immunology, 2022)
Young adults are now considered major spreaders of coronavirus disease 2019 (COVID-19) disease. Although most young individuals experience mild to moderate disease, there are concerns of long-term adverse health effects. The impact of COVID-19 disease and to which extent population-level immunity against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) exists in young adults remain unclear. We conducted a population-based study on humoral and cellular immunity to SARS-CoV-2 and explored COVID-19 disease characteristics in young adults. We invited participants from the Swedish BAMSE (Barn [Children], Allergy Milieu, Stockholm, Epidemiology) birth cohort (age 24-27 years) to take part in a COVID-19 follow-up. From 980 participants (October 2020 to June 2021), we here present data on SARS-CoV-2 receptor-binding domain–specific IgM, IgA, and IgG titers measured by ELISA and on symptoms and epidemiologic factors associated with seropositivity. Further, SARS-CoV-2–specific memory B- and T-cell responses were detected for a subpopulation (n = 108) by ELISpot and FluoroSpot. A total of 28.4% of subjects were seropositive, of whom 18.4% were IgM single positive. One in 7 seropositive subjects was asymptomatic. Seropositivity was associated with use of public transport, but not with sex, asthma, rhinitis, IgE sensitization, smoking, or body mass index. In a subset of representative samples, 20.7% and 35.0% had detectable SARS-CoV-2 specific B- and T-cell responses, respectively. B- and T-cell memory responses were clearly associated with seropositivity, but T-cell responses were also detected in 17.2% of seronegative subjects. Assessment of IgM and T-cell responses may improve population-based estimations of SARS-CoV-2 infection. The pronounced surge of both symptomatic and asymptomatic infections among young adults indicates that the large-scale vaccination campaign should be continued.